Tanggungjawab Notaris Atas Akta Yang Dibuatnya Ditinjau Berdasarkan Hukum Pidana - Mitha Irza Noor El Islam; Sukirno Sukirno; Adya Paramita Prabandari (Notarius, 2021)
The Law on Notary Position does not clearly regulate the responsibilities of the notary in criminal cases and the criminal responsibility of the deed he has drawn up. This article discusses issues regarding the legal consequences for a notary's deed in case of a criminal case and the responsibility of the notary for the deed he has made is reviewed under criminal law. The approach method used is normative juridical. The analysis used in this research is descriptive qualitative. The results of the research state that the legal consequences for the notary deed in case of a criminal case must be proven based on a judge's decision in court. If the deed creates a case for the parties concerned, the notary can be prosecuted for punishment. The provisions of Article 66 of the UUJN-P are imperative for the Police, the Attorney General's Office, or the Judge. UUJN-P does not regulate criminal sanctions against notaries, so if a criminal violation occurs by a notary, the sanctions contained in the Criminal Code may be imposed.Keywords: responsibility; notary; deed; criminal lawAbstrakAbstrak Undang-Undang Jabatan Notaris tidak mengatur secara jelas terkait tanggungjawab bagi notaris dalam kasus pidana dan tanggung jawab pidana dari akta yang telah dibuatnya. Artikel ini membahas permasalahan mengenai akibat hukum bagi akta notaris jika terjadi kasus pidana serta tanggungjawab notaris atas akta yang dibuatnya ditinjau berdasarkan hukum pidana. Metode pendekatan yang digunakan adalah yuridis normatif. Analisis yang digunakan penelitian ini adalah deskriptif kualitatif. Hasil penelitian menyatakan bahwa akibat hukum bagi akta Notaris jika terjadi perkara pidana harus dibuktikan berdasarkan putusan hakim di pengadilan. Apabila akta tersebut menimbulkan perkara bagi para pihak yang berkepentingan, notaris dapat dituntut untuk dipidana. Ketentuan Pasal 66 UUJN-P tersebut bersifat imperatif bagi pihak Kepolisian, Kejaksaan, atau Hakim. UUJN-P tidak mengatur sanksi pidana terhadap notaris, maka apabila terjadi pelanggaran pidana oleh notaris dapat dikenakan sanksi yang terdapat dalam KUHPidana. Kata kunci: tanggungjawab; notaris; akta; hukum pidanaThe Law on Notary Position does not clearly regulate the responsibilities of the notary in criminal cases and the criminal responsibility of the deed he has drawn up. This article discusses issues regarding the legal consequences for a notary's deed in case of a criminal case and the responsibility of the notary for the deed he has made is reviewed under criminal law. The approach method used is normative juridical. The analysis used in this research is descriptive qualitative. The results of the research state that the legal consequences for the notary deed in case of a criminal case must be proven based on a judge's decision in court. If the deed creates a case for the parties concerned, the notary can be prosecuted for punishment. The provisions of Article 66 of the UUJN-P are imperative for the Police, the Attorney General's Office, or the Judge. UUJN-P does not regulate criminal sanctions against notaries, so if a criminal violation occurs by a notary, the sanctions contained in the Criminal Code may be imposed.Keywords: responsibility; notary; deed; criminal lawAbstrakUndang-Undang Jabatan Notaris tidak mengatur secara jelas terkait tanggungjawab bagi notaris dalam kasus pidana dan tanggung jawab pidana dari akta yang telah dibuatnya. Artikel ini membahas permasalahan mengenai akibat hukum bagi akta notaris jika terjadi kasus pidana serta tanggungjawab notaris atas akta yang dibuatnya ditinjau berdasarkan hukum pidana. Metode pendekatan yang digunakan adalah yuridis normatif. Analisis yang digunakan penelitian ini adalah deskriptif kualitatif. Hasil penelitian menyatakan bahwa akibat hukum bagi akta Notaris jika terjadi perkara pidana harusdibuktikan berdasarkan putusan hakim di pengadilan. Apabila aktatersebut menimbulkan perkara bagi para pihak yang berkepentingan,notaris dapat dituntut untuk dipidana. Ketentuan Pasal 66 UUJN-P tersebut bersifat imperatif bagi pihak Kepolisian, Kejaksaan, atau Hakim. UUJN-P tidak mengatur sanksi pidana terhadap notaris, maka apabila terjadi pelanggaran pidana oleh notaris dapat dikenakan sanksi yang terdapat dalam KUHPidana.Kata kunci:    tanggungjawab; notaris; akta; hukum pidana